Television and the Case Study Method—An Experiment - LeBreton, Preston P. (Academy of Management Journal, 1958)
Presents an experiment which examined the use of a television (TV) case method of instruction to students working towards a Master of Business Administration °. Information on the TV studio used; Description of the panel members involved in the study; Recommendations for those who might be encouraged to experiment further with case instruction via TV.